2018
DOI: 10.1542/peds.2018-1245
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Hand Hygiene Program at Child Care Centers: A Cluster Randomized Trial

Abstract: OBJECTIVES: Respiratory infections (RIs) are an important cause of morbidity and excessive antibiotic prescriptions in children attending day care centers (DCCs). We aimed to assess the effectiveness of an educational and hand hygiene program in DCCs and homes in reducing RI incidence and antibiotic prescriptions in children. METHODS: A cluster, randomized, controlled, and open study of 911 children aged 0 to 3 years attending 24 DCCs in Almería (Spain) with an 8-month follow-up. Two intervention groups of DCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
0
35
0
4
Order By: Relevance
“…Additionally, the dynamics of SARS-CoV-2 transmission are not fully understood. While studies have shown the use of alcohol-based hand sanitizers to be correlated with the reduction of respiratory illness, 9 , 10 more evidence is needed to understand the relative impact of hand hygiene and alcohol-based hand sanitizers at preventing COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dynamics of SARS-CoV-2 transmission are not fully understood. While studies have shown the use of alcohol-based hand sanitizers to be correlated with the reduction of respiratory illness, 9 , 10 more evidence is needed to understand the relative impact of hand hygiene and alcohol-based hand sanitizers at preventing COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…These programs were based on the fact that caregivers’ knowledge about infectious diseases, their modes of transmission, and infection control practices were marginal. After the implementation of these programs (mainly health education programs about hand hygiene and environmental cleaning), the infectious diseases rates among children and caregivers were reduced, enhancing the fact that level of knowledge and infection control practices among those caregivers was really poor [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mencuci tangan dengan sabun merupakan salah satu kegiatan yang dapat mencegah penyakit menular pada tubuh (Clark et al, 2016). Mencuci tangan menggunakan sabun dapat mengatasi penyebaran virus, dan berbagai penyakit (Azor-Martinez et al, 2018). Pembiasaan pola hidup sehat dan bersih dilakukan terus menerus agar menjadi kebiasaan baik bagi anak.…”
Section: Hasil Dan Pembahasanunclassified